Serum concentrations, pharmacokinetic/pharmacodynamic modeling, and effects of dexamethasone on inflammatory mediators following intravenous and oral administration to exercised horses. Issue 8 (22nd June 2020) - Knych, Heather K.; Weiner, Daniel; Arthur, Rick M.; Baden, Russell; McKemie, Daniel S.; Kass, Philip H.
Abstract: Corticosteroids are potent anti‐inflammatory drugs and as such are commonly administered to performance and racehorses. The objectives of the current study were to describe blood and urine concentrations and the pharmacokinetics and effects on cortisol and inflammatory mediator concentrations, following intravenous and oral administration to 12 exercised horses. Horses received an intravenous administration of 40 mg of dexamethasone sodium phosphate and 20 mg of dexamethasone tablets with a 4 week washout in between administrations. Blood and urine samples were collected prior to and for up to 96 hours post drug administration. Whole blood samples were collected at various time points and challenged with lipopolysaccharide or calcium ionophore to induce ex vivo synthesis of eicosanoids. The concentrations of dexamethasone and eicosanoids were measured using LC–MS/MS and the concentrations from both routes of administration fit simultaneously using a three‐compartment pharmacokinetic model. A turnover model with inhibition of Kin gave an adequate fit to the dexamethasone‐cortisol PKPD data. Serum and urine dexamethasone concentrations were at the limit of quantitation at 96 and 48 hours post administration, respectively. The volume of distribution, systemic clearance, and terminal half‐life was 0.907 L/kg, 7.89 mL/h/kg, and 1.34 h, respectively. The IC50 for cortisol suppression was 0.007 ng/mL. Stimulation of dexamethasone treated blood with lipopolysaccharide and calcium ionophore resulted in an inhibition of inflammatory biomarker production for a prolonged period of time post drug administration. The results of this study suggest that dexamethasone has a prolonged anti‐inflammatory effect following intravenous or oral administration to horses. Abstract : Following intravenous and oral administration of 30 and 20 mg of dexamethasone, respectively, serum concentrations were at or below the LOQ by 96 hours. Suppression of endogenous cortisol was observed for 96 and 120 hours for intravenous and oral administration, respectively. Prolonged inhibition of a number of eicosanoids, including TXB2, PGE2, LTB4, and 15(S)‐HETE was observed in serum collected from horses treated with dexamethasone following ex vivo stimulation with LPS and calcium ionophore.